Conceptual Aspects of Innovation Management in Offline and Networked Production Systems - Mansur F. SAFARGALIEV; Gaziz F. MINGALEEV; Ruslan F. GARIFULLIN; Bulat R. GAREEV (Communications of International Proceedings, 2020)
The digital economy makes new demands on the models of company management, demands from them fundamentally new approaches to innovation, including in the field of innovative entrepreneurship. Among the important prerequisites for the network transformation of the innovative activity of modern production systems in the digital environment, the author attributed the following: the emergence of new technological structures; the emergence of new models of innovation management based on the development of organizational and communication mechanisms; expanding the availability of resources in the digital environment and increasing the economic freedom of participants in innovative activities.
Keywords: Network; Production System; Digital Economy; Ecosystem; Infrastructure.